Stereoselective synthesis of β-proline derivatives from allylamines via domino hydroformylation/Wittig olefination and Aza-Michael addition - Farwick, Andreas; Helmchen, Günter (Advanced synthesis & catalysis, 2010)
Under appropriate reaction conditions, a domino hydroformylation/Wittig olefination can be accomplished with derivatives of allylamines and stabilized Wittig ylides. A further highly diastereoselective aza-Michael reaction yields β-proline derivatives. These are, for example, useful as building blocks for alkaloid syntheses.
Gesehen am 13.02.2023